2020
DOI: 10.1016/j.jinf.2019.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Specificity, kinetics and longevity of antibody responses to avian influenza A(H7N9) virus infection in humans

Abstract: s u m m a r yObjectives: The long-term dynamics of antibody responses in patients with influenza A(H7N9) virus infection are not well understood. Methods: We conducted a longitudinal serological follow-up study in patients who were hospitalized with A(H7N9) virus infection, during 2013-2018. A(H7N9) virus-specific antibody responses were assessed by hemagglutination inhibition (HAI) and neutralization (NT) assays. A random intercept model was used to fit a curve to HAI antibody responses over time. HAI antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Patients who survive critical illness might mount higher antibody responses, which can persist for longer periods compared with those with nonsevere disease. 14 The antibody levels, however, are confounded by other treatments, such as antiviral drugs, steroids, and IV immunoglobulin. 15 A recent animal model indicated that antibodies produced from SARS-CoV-2 infection could protect from subsequent exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who survive critical illness might mount higher antibody responses, which can persist for longer periods compared with those with nonsevere disease. 14 The antibody levels, however, are confounded by other treatments, such as antiviral drugs, steroids, and IV immunoglobulin. 15 A recent animal model indicated that antibodies produced from SARS-CoV-2 infection could protect from subsequent exposures.…”
Section: Discussionmentioning
confidence: 99%
“…The weakness of the study should be noted that the clinical relevance of antibody titers in protecting against subsequent SARS-CoV-2 infection is uncertain. Compared to ELISAs, neutralization assays require virus culture, are much more labor-intensive, and need to be conducted in laboratories with higher biosafety levels [15,16]. We are currently conducting neutralization studies to further investigate whether ELISA results were correlated with neutralization results so far as to substitute for the neutralization test in resource-limited situations.…”
Section: Discussionmentioning
confidence: 99%
“…Convalescent plasma therapy (CPT) is passive immunotherapy that works to neutralize the antibodies against pathogens and is obtained from the plasma of recovery patients. This treatment strategy has been used in the treatment of outbreaks of infectious diseases such as influenza, [ 24 ] measles, hemorrhagic fever in Argentina, Zika virus infection, [ 25 ] MERS, [ 26 ] and SARS. Research on plasma replacement antibodies containing highly potent anti-SARS-CoV-2, donated by recovered patients, has shown promising results, and these neutralizing antibodies have been used in the treatment of critically ill COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%